L’utopia dell’aldilà in Luciano di Samosata - Alberto Camerotto (Annali Online dell'Università di Ferrara. Sezione Lettere)
The aim of this essay is to analyse and describe the characteristics of the Hereafter in Lucian as a paradoxical utopia with a cynical origin. Specifically, in Hades we can find the egalitarian rules of democracy as would be conceivable on Earth. Also, the Hereafter is the realm of freedom of speech, satire and laughter, where we can meet Menippus, Diogenes and Crates. Of course, as we shall see, not all the wordly problems are eliminated.